Parboiled germinated rice production using a new method - Thatchapol Chungcharoen; Pornpit Onboon; Sansanee Sansiribhan (My University, 2020)
The process complexity is the main problem for parboiled germinated rice (PGR) production. The PGR production using the new method (germinating and drying using hot air fluidized bed combined with halogen lamp) can decrease the complexity of process and also provided the good quality of PGR when comparing with PGR production using traditional method (germinating, steaming and drying using hot air fluidized bed). The new method provided the higher drying rate, leading to faster decrease of moisture content and higher increase of grain temperature. This caused the lower whiteness index. It also provided the lower degree of gelatinization. However, the percentage of head rice yield of PGR with new method was not significantly different when comparing with PGR production using traditional method. For Specific Energy Consumption (SEC), the PGR production using the new method provided the lower SEC value than PGR production using traditional method.
Keywords: Steaming; GABA and Rice Research